Supporting Staff Development through change in Learning Technologies in Higher Education - Burns, Robert (2007)
The challenge to enhance staff development processes in a way that reflects a changing global learning environment and supports academic staff in their efforts to integrate the affordances of the rapidly changing learning technology opportunities into their learning environments is a common one for many of the institutions in higher education. This dissertation records a response to this challenge in the context of a higher education institution in Ireland. In an attempt to understand how a selected cross-section of the academic staff of the institution were aware of the pedagogical underpinning required for the effective use of learning technologies, a grounded theory approach was used to interpret their individual and degree group responses to a guided interview process. Co-raters independently identified learning issues raised by the informants in the recorded data, and, reliability tests were performed on the results from the co-raters. Having identified the highest occurring learning issues from this phase of analysis these key issues were taken back to the informants for further discussion in focus groups aimed at clarifying their thinking regarding these issues. Cluster Analysis was used at the next phase to inform how best to analyse the recordings of the focus groups. The application of grounded theory methods is set out in a way to provide transparency, seeking to respond to the, sometimes critical, comment made regarding the use of this methodology. The use of grounded theory methods enabled themes to be identified from the focus group data leading to a definition of theory that affirmed some existing theoretical positions and extended others by more specific identity of the role that academic management need to play in understanding, and planning for the integration of, the use of learning technologies by the academic staff for whom they have management responsibility.